2019
DOI: 10.1088/1755-1315/399/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Spatial model of land use/land cover change dynamics and projection of Cisadane Watershed

Abstract: One of the major problems in watershed management is to balance the ecological function and fulfillment of human needs in a limited area. Rapid land-use changes often occurred as a result of human activities. Regular monitoring of land-use change dynamics is needed to help the government in making a decision within the area. Cisadane watershed is one of 15 priority watersheds in West Java Province, which categorized as very critical. This study aims to: 1) analyze land use/land cover (LULC) change dynamics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Meanwhile, The Agricultural Land Statistics showed that in 2014-2018, the total area of paddy fields in Bogor Regency continued to decline, with the land conversion rate reaching 4,579 hectares per annum [11]. It can be said that in the last two decades, large-scale conversion of agricultural land in Bogor Regency is taking place, particularly the conversion of food cropland into other uses, such as for settlements, industrial estates, and different types of development of nonagricultural use [12,13,14]. These massive land-use changes become one of the strategic issues for the future regional development of the Bogor Regency.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, The Agricultural Land Statistics showed that in 2014-2018, the total area of paddy fields in Bogor Regency continued to decline, with the land conversion rate reaching 4,579 hectares per annum [11]. It can be said that in the last two decades, large-scale conversion of agricultural land in Bogor Regency is taking place, particularly the conversion of food cropland into other uses, such as for settlements, industrial estates, and different types of development of nonagricultural use [12,13,14]. These massive land-use changes become one of the strategic issues for the future regional development of the Bogor Regency.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the division of functional areas, there are two distinct directions: urban agglomerations (Wang et al, 2021;Shan et al, 2020) and nature reserves (Xin et al, 2023). Moreover, based on the natural units, there are three different directions: watersheds (Wulandari et al, 2019), plateaus (Zhang et al, 2021), and mountains (Poyatos et al, 2003;Xystrakis et al, 2017). c. Local scales include counties (Karimi et al, 2018;Cheruto et al, 2016), villages, etc.…”
Section: Introductionmentioning
confidence: 99%